Solar Tracking Techniques and Implementation in Photovoltaic Power Plants: a Review: Solar Tracking Techniques and Implementation in Photovoltaic Power Plants - Khalil, Fazli A.; Asif, Muhammad; Anwar, Shahzad; Haq, Sana ul; Illahi, Farman (Proceedings of the Pakistan Academy of Sciences: A. Physical and Computational Sciences, 2021)
Electricity is one of the basic needs of life. Emission of harmful gases during the process of electricity generation leads to greenhouse affects. However, by employing photovoltaic (PV) panels, electricity can be generated without creating air, noise and water pollution caused by the emission of harmful gases. Geographically, Pakistan is located in a region of the world where solar irradiance is approximately 2000 KWh/m2. In recent decades, grid-connected PV power plants have been implemented worldwide to fulfill the power requirements. Usually, these power plants are mounted fixed. However, with advancement in technology solar trackers have increased the yield. In this study, after reviewing and analyzing various PV tracking techniques, an open-loop single axis technique is suggested for use in the huge PV power plants.